Bless me Father - D'Offizi, Mario (Book collections on Project MUSE., 2014)
Bless Me Father is the true story of an incredible South African life. Born into a violent and broken family, and growing up in a variety of institutions, Cape Town based poet and writer Mario d'Offizi tells his remarkable, often shocking and ultimately inspiring life adventure - one that spans several decades in a country undergoing radical change. From his tough days at Boys Town to wild years in the advertising world, a stint in the restaurant business and a sharp edged journalistic adventure in the DRC, d'Offizi tells his critically acclaimed story with the unfailing sensitivity and warmth of a true poet.